Practicing history : new directions in historical writing after the linguistic turn - Spiegel, Gabrielle M. (New York : Routledge, 2005)
"Gabrielle Spiegel presents an essential new collection of key articles that examine the current status of the debate over the 'linguistic turn', and attempt to rethink the practice of history in light of its implications. These are writings that operate within the framework of the linguistic turn, yet seek to move beyond its initial formulation and reception. The volume offers a synoptic overview of the last twenty-five years of theoretical analysis of historical writing, with a critical examination of the key concepts and positions that have been in debate. This collection delineates the emergence of a new 'practice theory' as a possible paradigm for future historical interpretation concerned with questions of agency, experience and the subject. Articles drawn from a mix of critical thinkers and practicing historians are drawn together along with clear and thorough editorial material. Complex ideas at the forefront of historical practice are revealed and made accessible to students, while for their teachers and other historians this new survey is an indispensable and timely read"--Provided by publisher.
Is all the world a text? From social history to the history of society two decades later / Geoff Eley -- The determinist fix : some obstacles to the further development of the linguistic approach to history in the 1990s / Gareth Stedman Jones -- The concept(s) of culture / William H. Sewell, Jr. -- Agency in the discursive condition / Elizabeth Deeds Ermarth -- Individual experience and cultural order / Marshall Sahlins -- The constitution of society : outline of the theory of structuration : elements of the theory of structuration / Anthony Giddens -- A theory of structure : duality, agency and transformation / William H. Sewell, Jr. -- How to be an intentionalist / Mark Bevir -- Outline of the theory of practice : structures and the habitus / Pierre Bourdieu -- The evidence of experience / Joan Scott -- The practice of everyday life : "making do" : uses and tactics / Michel de Certeau -- Language and the shift from signs to practices in cultural inquiry / Richard Biernacki -- Toward a theory of social practices : a development in culturalist theorizing / Andreas Reckwitz.
Includes bibliographical references (p. 262-268) and index.
Keywords: HISTORIOGRAPHY; LANGUAGE AND HISTORY; WRITING HISTORY; HISTORY